Wideband Dual-Polarized Binary Coding Antenna With Wide Beamwidth and Its Array for Millimeter-Wave Applications - Wang, Lei; Geng, Junping; Wang, Kun; Zhou, Han; Ren, Chaofan; Wu, Haobo; Zhao, Xiaonan; He, Chong; Liang, Xianling; Zhu, Weiren; Jin, Ronghong (IEEE antennas and wireless propagation letters, 2020)
A novel millimeter-wave (mm-Wave) binary coding antenna with broadband, dual-polarization, and wide beamwidth is proposed, and its broad-angle scanning array is also studied. The element employs the stacked patches, where the optimal middle parasitic patch and top driven patch are introduced to broaden the bandwidth and beamwidth. The driven and parasitic patches are realized by series of small units optimized by binary code. The measured results for the proposed antenna prototype agree well with the simulated ones, showing a wide impedance bandwidth and good port isolation from 21.8 to 33.2 GHz (FBW = 41.5%). The measured half-power beamwidth is between 128 ^{° } and 157 ^{° } over the operating bandwidth. The element was then extended to an eight-element phased array. The measured results demonstrate that the array with a broad scanning angle more than 100 ^{° } over the available band can be achieved.